La banalité de l'échange. Entretien avec Paola Tabet - Mathieu Trachman (Genre, Sexualité et Société)
In this interview, the anthropologist reflects upon her theoretical and personal development and the process that led her to construct the concept of sexual-economic exchange. She integrates this concept in the totality of her work on the sexual division of labour, the management of reproduction, and the control of sexuality.  She also reflects upon applications of the notion of sexual-economic exchange, notably the limits of using it principally in regards to what one calls “sex work” and the difficulty of thinking of sexual-economic exchange as a continuum.  Paola Tabet’s work thus emerges as a set of theoretical and political tools whose objective is to understand and deconstruct gender relations and the foundation of male domination.